Sustainable Management of Water Resources in Urban Areas - Fidani, Drenushe; Violeta Gesovska (Juniper Publishers, 2019)
Water is the basis for survival of the mankind, but its spatial and temporal distribution is extremely uneven. In their activities, people use water, affecting at the same time the natural balance, inflicting thus major consequences for the human, the overall living and plant environment. This paper is aimed at illustrating some of the challenges faced by competent policy makers and planners in managing water resources for the purpose of implementation of the sustainable development goal related to water management and sanitation. Through specific problems in the territory of the R. of North Macedonia, a comparative analysis of sustainable development goals and experience in urban areas, specifically in the city of Gostivar, is made. It is concluded that steps have certainly been taken for the last three years, but a lot has still to be done regarding observation of legal obligations in the sphere of sustainable management of water resources in urban areas.
Keywords: Sustainable development; Water resources management; Urban area